Real-time market price monitoring: Current dynamics in southern Rwanda - Warner, James; Manners, Rhys (International Food Policy Research Institute, 2024)
Recent collaborative CGIAR research has developed a prototype for tracking district-level costs of a healthy diet using monthly eSoko data.1 High frequency monitoring of diets allows for near real-time generation of insights on price impacts on diet costs. The temporal richness of this data allows for immediate analytics of current food system events. This research provides an analysis of district-level price movements of healthy diet compositions, as well as food prices that compose the diet. We use this prototype to demonstrate how eSoko data could be used for monitoring an economic shock and how to evaluate the effects in near real time. The general goal is to demonstrate a potential early warning system that could improve the menu of policy choices for enhanced resilience.